The Increase of Middle Class in a Public School: Improvement or Exclusion? - Débora Cristina Piotto (Universidade Estadual Paulista Júlio de Mesquita Filho, 2007)
The goal of this article is to discuss the relationship between educators of a public school and parents that came from private schools. Such discussion is based on a research that tried to answer the following question: "what are the repercussions on lower class children due to the increase of middle classes students in public schools?" In order to answer that question, we have carried out an ethnological study in a school in the city of Ribeirão Preto in which this phenomenon was evident. Not only observations were made, but also interviews with director, adviser, teachers and parents. The results of the field research were surprising since they show that the relation between students from the middle class and the public school is much more complex than supposed.